2016
DOI: 10.1108/ijmf-08-2015-0156
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and dividend strategy: lessons from Australia

Abstract: The purpose of this paper is to empirically investigate the effects of corporate governance on the dividend payout in Australia where dividend payout remains high and the corporate governance system has been strengthened. Design/methodology/approach: A self-constructed governance index from 2001 to 2013 is used to test the effect of corporate governance on dividend payouts. Two versions of the indexes, and the traditionally emphasized governance elements, such as board structure, are also used for the robustne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 91 publications
3
33
1
4
Order By: Relevance
“…The IOS shows the existence of favorable growth prospects or opportunities, reflecting that Based on Table 1, dividend policy reflected through the value of the Dividend Payout Ratio (DPR) shows an unstable and fluctuating value and tends to be avoided by investors who want certainty in return on investment. The company needs to maintain its dividend policy on an ongoing basis so that investors can interpret the situation as a signal on the company's performance (Shamsabadi & Chung, 2016). The total assets of the agricultural sec-Dividend policy, investment opportunity set, free cash flow, and company performance: Indonesian's agricultural sector Choiri Chosiah, Budi Purwanto, Wita Juwita Ermawati | 405 | the company can manage additional share capital in increasing productive assets having the potential to increase company growth (Pratiwi, 2016).…”
Section: Abstrakmentioning
confidence: 99%
See 2 more Smart Citations
“…The IOS shows the existence of favorable growth prospects or opportunities, reflecting that Based on Table 1, dividend policy reflected through the value of the Dividend Payout Ratio (DPR) shows an unstable and fluctuating value and tends to be avoided by investors who want certainty in return on investment. The company needs to maintain its dividend policy on an ongoing basis so that investors can interpret the situation as a signal on the company's performance (Shamsabadi & Chung, 2016). The total assets of the agricultural sec-Dividend policy, investment opportunity set, free cash flow, and company performance: Indonesian's agricultural sector Choiri Chosiah, Budi Purwanto, Wita Juwita Ermawati | 405 | the company can manage additional share capital in increasing productive assets having the potential to increase company growth (Pratiwi, 2016).…”
Section: Abstrakmentioning
confidence: 99%
“…The application of corporate governance in the company is also known to influence the company's dividend policy. Shamsabadi & Chung (2016); Jiraporn, Kim, & Kim (2011);Elmagrhi et al (2018); demonstrated a positive relationship between the Jurnal Keuangan dan Perbankan Volume 23, Issue 3, July 2019: 403-417 | 406 | quality of governance and dividend payments, where good governance will make managers release more of their profits as dividends. Jiraporn & Ning (2006) showed that dividend payments are inversely proportional to shareholder power.…”
Section: Abstrakmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fifth paper, Shamsabadi et al (2016) examine dividend policy as a means of ensuring that profits are distributed to investors rather than consumed by management through private benefits. While committing cash flow to interest or dividends as a means of stemming agency problems has a long history of examination (i.e.…”
Section: Guest Editorialmentioning
confidence: 99%
“…Shamsabadi et al (2016) study dividends as a possible solution to reducing free cash flow, noting how payout differs depending on firm-level corporate governance and taxation regime while Li et al (2016) ask whether corporate social responsibility (CSR) has become a vehicle for managers to promote their own public image at the expense of shareholders.…”
Section: The Special Issuementioning
confidence: 99%